MEMBANGUN JEMBATAN PERADABAN: PERAN DAKWAH ISLAM DALAM MENDORONG DIALOG DAN KERJASAMA ANTARA ISLAM DAN BARAT - Sipayung, Nurhasanah; Annisaa, Fadhilah Nur; Nasution, Andini Rahmadhani; Ritonga, Atha Putra Asri; Putra, Fairuz Zahara; Sitepu, Zildjian Zubi Zuchry; Aini, Husna; Windari, Sri (Cahaya Ilmu Bangsa Institute, 2025)
This article examines the role of Islamic da'wah in bridging the gap between Islam and the West, which is often characterized by misunderstandings and conflicts. This research aims to identify effective da'wah strategies in fostering constructive dialogue and mutually beneficial cooperation. Through a literature review approach, this article analyzes various dialogue-oriented da'wah models, emphasizing the importance of inclusive communication, respect for differences, and a focus on universal values. The main finding shows that da'wah that emphasizes common ethical and moral values, and promotes a correct understanding of Islamic teachings, can significantly enhance the potential for cooperation between the two civilizations. This article concludes that Islamic da'wah has a crucial role in building more harmonious and productive relations between Islam and the West.